Prathers mark 50th anniversary (Raton, New Mexico Raton Range, 1992)
Newspaper Article on the 50th Anniversary of Melvin & Lula Prather
Master list item #: 9
File location is in the Raton File Cabinet
Keywords: Prather, Melvin S; Prather, Lula; Palonimo, Ben; Palomino, Inez; Trinity United Methodist Church; Luby's Cafeteria; First Methodist Church; First United Methodist Church; Gate City Lodge, No. 11; AF&AM; Rotary Club; Queen Esther Chapter; Order of Eastern Star; Biography; Local History; Life and Customs; Anniversary; Celebration; Marriage; Raton, New Mexico; Waco, Texas; Arlington, Texas; El Paso, Texas; Crane, Texas; Waxahachie, Texas; Dallas, Texas; Grandview, Texas; Fort Worth, Texas